Relationships Between Blood Pressure and 24‐Hour Urinary Excretion of Sodium and Potassium by Body Mass Index Status in Chinese Adults. Issue 12 (29th August 2015) - Yan, Liuxia; Bi, Zhenqiang; Tang, Junli; Wang, Linhong; Yang, Quanhe; Guo, Xiaolei; Cogswell, Mary E.; Zhang, Xiaofei; Hong, Yuling; Engelgau, Michael; Zhang, Jiyu; Elliott, Paul; et al.
Abstract : This study examined the impact of overweight/obesity on sodium, potassium, and blood pressure associations using the Shandong‐Ministry of Health Action on Salt Reduction and Hypertension (SMASH) project baseline survey data. Twenty‐four–hour urine samples were collected in 1948 Chinese adults aged 18 to 69 years. The observed associations of sodium, potassium, sodium‐potassium ratio, and systolic blood pressure (SBP) were stronger in the overweight/obese population than among those of normal weight. Among overweight/obese respondents, each additional standard deviation (SD) higher of urinary sodium excretion (SD=85 mmol) and potassium excretion (SD=19 mmol) was associated with a 1.31 mm Hg (95% confidence interval, 0.37–2.26) and −1.43 mm Hg (95% confidence interval, −2.23 to −0.63) difference in SBP, and each higher unit in sodium‐potassium ratio was associated with a 0.54 mm Hg (95% confidence interval, 0.34–0.75) increase in SBP. The association between sodium, potassium, sodium‐potassium ratio, and prevalence of hypertension among overweight/obese patients was similar to that of SBP. Our study indicated that the relationships between BP and both urinary sodium and potassium might be modified by BMI status in Chinese adults.